PERANCANGAN DAN PEMBUATAN SISTEM INFORMASI SUPPLY CHAIN MANAGEMENT BERBASIS WEB PADA PT. USIMPEL INOVASI INDONESIA - Muhammad Wendy Danendra Pohan; Bunga Tarisa; Muhammad Yogie Pratama; Sharyanto Sharyanto; Raditya Galih Whendasromo (Journal of Information System, Informatics and Computing, 2026)
PT Usimpel Inovasi Indonesia is a broadband internet service provider that still faces challenges in Supply Chain Management (SCM) due to the absence of an integrated system. Item requests are conducted via email without internal documentation, procurement is handled manually, and inventory management relies on spreadsheets, which are prone to errors. This study aims to design and develop a web-based Supply Chain Management information system to improve efficiency and data accuracy. The research methods include observation, interviews, and literature study. The system is developed using PHP programming language and MySQL database and is modeled using Unified Modeling Language (UML). Additionally, the system applies Reorder Point (ROP) and safety stock methods to support inventory control. The result of this study is a web-based information system capable of managing request, procurement, payment, and reporting processes in an integrated manner. Black Box testing shows that the system functions as expected. This system is expected to enhance SCM management effectiveness and reduce data recording errors